Solution processed hybrid solar cells : structure and material considerations - Sun, Shuangyong (2015)
Hybrid solar cells (HSCs) combine the advantages of both organic and inorganic materials, and can therefore have the potential to realize high performance at low production cost. Nevertheless, the performance of state-of-the-art HSCs is still low currently, mainly due to a lack of percolation pathways for charge transport in the photoactive layer after thin film deposition. On top of this, the physical distance between conjugated polymers and inorganic nanocrystals (NCs) is large and can therefore retard the charge transfer between them. In this thesis, two different approaches have been developed to address these issues. In the first approach, the integration of self-assembled nanostructures into HSCs to boost device performance has been demonstrated. It was found that after the incorporation of pre-assembled poly(3-hexylthiophene) (P3HT) nanofiber, solar cells based on cadmium selenide (CdSe) NCs showed better performance than those solar cells containing non-assembled P3HT. The enhanced efficiency mainly resulted from the increase in JSC, which could be attributed to the enhanced light absorption and better charge transport due to the presence of P3HT nanofiber. To improve the interaction between P3HT nanofiber and CdSe NCs, pyridine terminated low molecular weight P3HT (P3HTL-py) has been synthesized and incorporated into solar cells. The presence of favorable interaction between P3HTL-py and CdSe NCs was confirmed by solution stability study and XPS study. An ordered hybrid nanostructure was then prepared by co-assembly of P3HT and P3HTL-py in solution, followed by the attachment of CdSe NCs around the preformed functionalized nanofiber. When devices were fabricated from such hybrid solutions, the PCE increased by more than 20% compared to those devices based on pure P3HT nanofiber and CdSe NCs. It was believed that the enhanced performance was related to a more intimate donor-acceptor (D-A) interface, due to the presence of the additional interaction force. In another approach, methylammonium lead iodide (CH3NH3PbI3) has been synthesized and explored for photovoltaic application aiming to bypass challenges in obtaining optimal morphology in HSCs. It has been found that CH3NH3PbI3 exhibited excellent optical properties, with wide absorption window and large absorption coefficient. Besides, experiments based on ultrafast laser spectroscopy have shown that CH3NH3PbI3 had large and balanced electron and hole diffusion lengths. To evaluate the photovoltaic performance of CH3NH3PbI3, it was first coupled with CdSe NCs to make HSCs. It was found that solar cells based on such material combination could show decent performance (PCE of 2.6%). However, low fill factor (FF) limited the device performance, which was attributed to the high series resistance in the CdSe layer. To avoid this issue, subsequently PC61BM was applied to replace CdSe NCs to make solar cells. It has been found that CH3NH3PbI3/PC61BM bilayer solar cells could show a PCE of up to 5.23%, which is quite amazing considering the bilayer device structure adopted. The high performance was because the internal quantum efficiency (IQE) of the bilayer solar cell was close to 100%. This implied almost all the absorbed light contributed to the output current in such system.